2012
DOI: 10.1007/s12522-012-0120-2
|View full text |Cite
|
Sign up to set email alerts
|

Combination of recombinant follicle stimulating hormone with human menopausal gonadotrophin or recombinant luteinizing hormone in a long gonadotrophin‐releasing hormone agonist protocol: a retrospective study

Abstract: Use of rFSH combined with rhLH in long GnRH agonist assisted reproductive technology (ART) cycles was associated with more clinical pregnancies, recovery of more oocytes, and reduction in gonadotrophin use, suggesting that the superior purity and consistency of rFSH and rhLH may result in better clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Some of the recent studies suggest that the indicators for adding LH to an ART cycle are mid follicular (day 6) hypo-response to long GnRH agonist, no follicles > 10 mm, E2 < 200 pg/ml, endometrial thickness < 6 mm and baseline serum LH < 1.2 IU/ml on day 6. [ 8 25 ]…”
Section: Role Of Lh In Physiology: the Physiological Hormonal Interplmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the recent studies suggest that the indicators for adding LH to an ART cycle are mid follicular (day 6) hypo-response to long GnRH agonist, no follicles > 10 mm, E2 < 200 pg/ml, endometrial thickness < 6 mm and baseline serum LH < 1.2 IU/ml on day 6. [ 8 25 ]…”
Section: Role Of Lh In Physiology: the Physiological Hormonal Interplmentioning
confidence: 99%
“…[ 54 ] To achieve an optimal benefit Ramu et al suggested a dose of 75 IU/day of r-hLH for supplementation with r-HFSH. [ 25 ]…”
Section: Role Of Lh In Physiology: the Physiological Hormonal Interplmentioning
confidence: 99%
“…When compared with increasing rHFSH dose, adding rLH on days 8 was associated with a better cumulative implantation rate (14.2 vs 10.5) and cumulative pregnancy rate (37.2 vs 29.3). 20,34,35 There are recommendations for the use of LH supple mentation in the ongoing cycle for patients with a his tory of prior poor response and patients who exhibit a sub optimal response during long agonist ovarian stimulation protocols. There is a possibility to opti mize the ovarian response in both these patient groups through the addition of rLH.…”
Section: Patients At Risk Of Hyporesponse During Ovarian Stimulationmentioning
confidence: 99%
“…LH is also critical for the differentiation of mature follicle to the corpus luteum, and maintain normal luteal function to ensure proper gonadal functioning ( 13 ). In our earlier study, in 2012 we reported better pregnancy rates when we replaced the use of r-hFSH plus hMG with r-hFSH plus r-hLH combination ( 14 ). Interestingly, we observed variable responses among the women receiving r-hLH supplementation.…”
Section: Introductionmentioning
confidence: 99%